IMPLEMENTATION OF SALES PLANNING AND CONTROL OF RAW MATERIALS FOR THE CURRENT PRODUCTION PROCESS IN WINGKO COMPANY BAMBANG INDRAAYA BABAT LAMONGAN - Darianto, Darianto; Fauzi, Maulidza Nur (Journal of Industrial Engineering & Management Research, 2022)
Raw material control is the control carried out to carry out the production process at the company. Raw material control is very important. so that there is no delay in the availability of raw materials, the company must determine the supply of raw materials properly. The purpose of writing this scientific paper is to determine the implementation and control of raw materials for the smooth production process. In writing this scientific paper, the writer uses three methods, namely the interview method, the observation/observation method, and the literature study method. The results and conclusions of this scientific work can determine the sales plan for the future, it can be seen that the Wingko Bambang Indrajaya company produces the same sales composition as the previous year. The sales plan in 2021 is 132,000 while in 2020 it is 130,900 so the sales before and after being analyzed are the difference of 2,000 bags. The production process carried out by Wingko Bambang Indrajaya Babat is a continuous production process, this can be seen from the course of the production process, where the available materials are sufficiently used according to the work schedule, as well as keeping the flow of materials through the work steps. which exists. So that with a continuous production process or continuously will produce quality goods, namely wingko